2013
DOI: 10.1189/jlb.1012519
|View full text |Cite
|
Sign up to set email alerts
|

RAGE regulation and signaling in inflammation and beyond

Abstract: RAGE is a key molecule in the onset and sustainment of the inflammatory response. New studies indicate that RAGE might represent a new link between the innate and adaptive immune system. RAGE belongs to the superfamily of Ig cell-surface receptors and is expressed on all types of leukocytes promoting activation, migration, or maturation of the different cells. RAGE expression is prominent on the activated endothelium, where it mediates leukocyte adhesion and transmigration. Moreover, proinflammatory molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
301
2
14

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(320 citation statements)
references
References 174 publications
3
301
2
14
Order By: Relevance
“…Several studies have demonstrated interactions of MRP8/MRP14 with RAGE, focusing mainly on signaling pathways involving activation of MAPK p38 or the transcription factor NF-kB, including cellular mechanisms downstream of the MRP8/MRP14-RAGE interaction. However, no structural data regarding the ligand-receptor recognition sites have been described so far (21,22,24,38). Similar MRP8/MRP14-RAGE interactions were observed in a study done by Boyd et al (23) on purified cardiomyocytes, during which RAGE was coimmunoprecipitated with MRP8/ MRP14.…”
Section: Discussionmentioning
confidence: 78%
“…Several studies have demonstrated interactions of MRP8/MRP14 with RAGE, focusing mainly on signaling pathways involving activation of MAPK p38 or the transcription factor NF-kB, including cellular mechanisms downstream of the MRP8/MRP14-RAGE interaction. However, no structural data regarding the ligand-receptor recognition sites have been described so far (21,22,24,38). Similar MRP8/MRP14-RAGE interactions were observed in a study done by Boyd et al (23) on purified cardiomyocytes, during which RAGE was coimmunoprecipitated with MRP8/ MRP14.…”
Section: Discussionmentioning
confidence: 78%
“…Table I summarizes these RAGE ligands, including their chromosomal map locations, OMIM numbers, and a brief summary of each ligand. These can be found in greater detail in several references [Hudson et al, 2005;Kalea et al, 2009;Rojas et al, 2010;Yanai et al, 2009;Ramasamy et al, 2012;Kierdorf and Fritz, 2013]. Many RAGE ligands have various RAGE-independent effects as well [Logsdon et al, 2007;Sparvero et al, 2009].…”
Section: Rage Ligandsmentioning
confidence: 98%
“…AGE levels are lower in RAGE null mice, leading to the observation that glyoxalase 1 (Glo 1) a detoxifies methylglyoxal (MG). Thus, the action of RAGE not only contributes to the generation of AGE, but also to its perpetuation [Hudson et al, 2005;Kalea et al, 2009;Rojas et al, 2010;Ramasamy et al, 2012;Kierdorf and Fritz, 2013 Table II) [Sparvero et al, 2009;Rojas et al, 2010;Kierdorf and Fritz, 2013] …”
Section: The Role Of Rage In Cardiovascular Disease Based On Experimementioning
confidence: 99%
See 1 more Smart Citation
“…Interaction between full-length RAGE and AGEs causes enhanced expression of adhesion molecules, covering soluble vascular cell adhesion molecule-1 (sVCAM-1) together with cytokine tumor necrosis factor-alpha (TNF-α) [5] [6]. Conversely, activation of nuclear factor-kappa results in enhanced expression of pro-inflammatory genes [5] [7]; Circulating isoforms RAGE covering sRAGE is laminated from cell appearance via matrix metalloproteinases as well as endogenous secretory RAGE (esRAGE) [3] [4]. S100A12 refers to an inflammatory ligand of RAGE, which belongs to the S100 protein family.…”
Section: Introductionmentioning
confidence: 99%